Rehabilitation With Bridging Exercise In Stroke Patients: Systematic Review - Fauziah Rochmah, Ardianti; Septianingrum, Yurike; Lono Wijayanti; Umdatus Soleha (Chakra Brahmanda Lentera Institute, 2024)
Background: Stroke is a neurological disease that can result in weakness in part or all of the body, emphasizing the importance of early mobilization in post-stroke recovery. One of the fundamental physical exercises recommended is the bridging exercise. This article evaluates the impact of bridging exercises on stroke patients through a systematic review approach, focusing on their potential to improve rehabilitation outcomes. Methods: The methodology involved a systematic review of studies from 2020 to 2024, using journal databases such as Google Scholar, Science Direct, and PubMed. Keywords like